Absence of the psbH gene product destabilizes photosystem II complex and bicarbonate binding on its acceptor side in Synechocystis PCC 6803 - Komenda, Josef; Lupínková, Lenka; Kopecký, Jirí (European journal of biochemistry, 2002)
The PsbH protein, a small subunit of the photosystem II complex (PSII), was identified as a 6-kDa protein band in the PSII core and subcore (CP47-D1-D2-cyt b-559) from the wild-type strain of the cyanobacterium Synechocystis PCC 6803. The protein was missing in the D1-D2-cytochrome b-559 complex and also in all PSII complexes isolated from IC7, a mutant lacking the psbH gene. The following properties of PSII in the mutant contrasted with those in wild-type: (a) CP47 was released during nondenaturing electrophoresis of the PSII core isolated from IC7; (b) depletion of CO2 resulted in a reversible decrease of the QA- reoxidation rate in the IC7 cells; (c) light-induced decrease in PSII activity, measured as 2,5-dimethyl-benzoquinone-supported Hill reaction, was strongly dependent on the HCO3- concentration in the IC7 cells; and (d) illumination of the IC7 cells lead to an extensive oxidation, fragmentation and cross-linking of the D1 protein. We did not find any evidence for phosphorylation of the PsbH protein in the wild-type strain. The results showed that in the PSII complex of Synechocystis attachment of CP47 to the D1-D2 heterodimer appears weakened and binding of bicarbonate on the PSII acceptor side is destabilized in the absence of the PsbH protein.
Keywords: hydrogenuhličitany; fosforylace; Protein Binding; Photosystem II Protein Complex; oxidační stres; fotosyntetická reakční centra (proteinové komplexy); Phosphorylation; vazba proteinů; trypsin; Trypsin; fosfoproteiny; Oxidative Stress; Cyanobacteria; Bicarbonates; fotosystém II (proteinový komplex); Phosphoproteins; sinice; Photosynthetic Reaction Center Complex Proteins